Modelagem e análise de topologias para veículos aéreos não-tripulados do tipo multirotor - Sandi, Nathanyel (2017)
With an evolution of the multi-curral projects and their components, the designers have been having numerous options of combinations of components in the multirotor design phase, seeking better performance and lower cost. This leaves an open problem: as what the multirotor can achieve a good performance still in the design phase. One motivation to carry out this study is justified in that there are no works related to the survey of metrics and analysis of the performance of multirotors. As well as the factor there are no ways to measure a quality of projects and possibility of comparison, since there are several ways to design a multirotor for different applications. This work proposes an approach for an analysis of the design of multirotors in terms of their flight capacity, defining as characteristics of their rotors, weight and topology. The main objective is to present a way to qualify and quantify a multirotor aircraft to optimize its design. An approach approached for design design to support design requirements (such as power size, engine torque, frame topology), ensuring as required flight capabilities. As a result of this work, a set of indexes proposed to evaluate a multirole project quality, being: flight, stability, hover and heading. The sum of these indices compose the voleability index. This index offers a possibility of comparing the vehicle analysis according to the specifications of the engine assembly, propeller, topology and frame size. For a metric validation, an analysis of the topologies was performed, allowing a comparison for the performance function and their effort.